Legal Study in Takeover of Shares (Acquisition) in Limited Liability Companies in View of Law Number 40 of 2007 - Setiawan, Florencia Lavina (CV. Rayyan Dwi Bharata, 2024)
By owning shares, a person or company has the right to a portion of the company's assets and profits. When investors sell or buy shares of a particular company, they change their shareholdings. This condition is caused by market conditions, business performance and investors' strategic decisions. Information recorded on the stock exchange when a transaction occurs can influence the share price and ownership structure of the company. Changes in share ownership can impact market conditions and business performance. First, if shares of a business pass to more experienced or better-connected owners, this can improve management strategies and operational efficiency, which in turn can lead to better results for the company